COVID-19 and Co-production in Health and Social Care Research, Policy and Practice (Policy Press, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Groups most severely affected by COVID-19 have tended to be those marginalised before the pandemic and are now largely being ignored in developing responses to it.